MITIGASI KEGAGALAN ECDIS DALAM BERNAVIGASI PADA KAPAL FULL ECDIS DI MV. TEMBAGA SEA - Baharsyah, Rio Muhammad; Rizal Rochmansyah; Mashartanto, Achmad Ali; Yanti, Melda; Utama, Yusuf Pria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the factors causing the failure of the Electronic Chart Display and Information System (ECDIS) during navigation on the Full ECDIS vessel MV. Tembaga Sea, and to formulate effective mitigation strategies to minimize the risk of navigational disturbances. As the primary navigation system on a Full ECDIS vessel, ECDIS plays a crucial role in ensuring maritime safety; therefore, system failure may significantly impact ship operations. This research employed a descriptive qualitative method with a case study approach. Data collection was conducted through direct observation during the sea practice period (PRALA), in-depth interviews with the Chief Officer, Second Officer, and Third Officer, and documentation studies. Mitigation efforts include improving regular and scheduled maintenance, optimizing system and storage management, conducting training and familiarization on handling ECDIS failures, and strengthening supervision and evaluation by the company